Anne Conway’s Atemporal Account of Agency - Hope Sample (Ergo, An Open Access Journal of Philosophy)
This paper aims to resolve an unremarked-upon tension between Anne Conway’s commitment to the moral responsibility of created beings, or creatures, and her commitment to emanative, constant creation. Emanation causation has an atemporal aspect according to which God’s act of will coexists with its effect. There is no before or after, or past or future, in God’s causal contribution. Additionally, Conway’s constant creation picture has it that all times are determined via divine emanation. Creaturely agency, by contrast, is fundamentally temporal, occurring successively over time. It is unclear how creatures can count as emanative causes, which coexists with its effect, given that their agency is limited by time, proceeding from before to after, or past to future. Conway’s account of divine justice in the progress of time, however, requires that creatures are causally responsible. That is, moral responsibility requires causal responsibility. I propose that Conway’s distinction between vital motion and local motion enables a resolution of the tension. Vital motion contributes an atemporal aspect to creaturely agency so that creatures can count as secondary emanative causes.